EXPERIMENTAL EVIDENCE FOR CARBONATE STABILITY IN THE EARTHS LOWER MANTLE - Biellmann C.; Gillet P.; Guyot F.; Peyronneau J.; Reynard B. (My University, 1993)
We present experimental results on the stability of carbonates up to 50 GPa and at high temperatures (1500–2500 K). The experiments were conducted in a laser-heated diamond anvil cell and the run products were characterized by analytical transmission electron microscopy. Dolomite is shown to break down to aCaCO3 + MgCO3 assemblage at pressures between 20 and 50 GPa. No decarbonatation was evident, suggesting that carbonates remain stable under these conditions with respect to rocksalt oxide + CO2 assemblages. Equimolar mixed powders of dolomite + enstatite and dolomite + olivine were transformed into magnesite + calcic perovskite and into magnesite + calcic and magnesian perovskites + magnesiowu¨stite, respectively. The very strong partitioning of Ca in silicates suggests that magnesite is the stable carbonate in the presence of silicates in the Earth's lower mantle down to at least 1500 km. Finally, eutectoid or eutectic intergrowth of magnesiowu¨stite and magnesite is observed, suggesting a possible mutual solubility between these two phases at high pressures and high temperatures. Lower mantle magnesiowu¨stite may provide an alternative host for carbon in the Earth's lower mantle.